The Effect of Seasonal Cycles and Fish Price Fluctuations on Financial Literacy of Fishermen In Sifalaete Ulu Village, Gunungsitoli District - Masnia Zebua; Nanny Artatina Buulolo; Heniwati Gulo; Serniati Zebua (Economics and Business Journal (ECBIS), 2025)
The purpose of this study is to analyze, partially and simultaneously, the influence of seasonal cycles and fish price fluctuations on the financial literacy of fishermen in Sifalaete Ulu Village. Partially, this study aims to determine the effect of seasonal cycles on fishermen's financial literacy, as well as the effect of fish price fluctuations on fishermen's financial literacy. Simultaneously, this study aims to determine the effect of both variables together on fishermen's financial literacy. This study used a quantitative approach with data collected through questionnaires from 57 active fishermen. Data were analyzed using multiple linear regression to test the partial and simultaneous effects. The results show that partially, seasonal cycles have a negative and significant effect on fishermen's financial literacy, while fish price fluctuations have a positive and significant effect on fishermen's financial literacy. Simultaneously, seasonal cycles and fish price fluctuations have a significant effect on fishermen's financial literacy. Income uncertainty due to these two factors causes fishermen to experience difficulties in financial planning, lack savings or emergency funds, and tend to rely on debt. In addition, low levels of education and minimal financial literacy training also hinder effective financial management